2021
DOI: 10.1136/openhrt-2021-001640
|View full text |Cite
|
Sign up to set email alerts
|

Community-based aortic stenosis detection: clinical and echocardiographic screening during influenza vaccination

Abstract: BackgroundDegenerative aortic stenosis (AS), the most common valvular heart disease in the Western world, is often diagnosed late when the mortality risk becomes substantial. We determined the feasibility of AS screening during influenza vaccination at general practitioner (GP) surgeries in the UK.MethodsConsecutive subjects aged >65 years presenting to a GP for influenza vaccination underwent heart auscultation and 2D echocardiography (V-scan). Based on these findings, a patient management strategy was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In our cohort, 4.9% of the patients had concomitant moderate/severe MR and 8% had concomitant moderate/severe TR. The key findings of our analysis are summarized in the following: (1) Moderate/severe TR was associated with higher all-cause mortality at 1-year follow up; (2) Moderate to severe MR did not affect mortality at follow up; (3) Neither significant MR nor TR affected the TAVI procedure success or in-hospital death; (4) In multivariate analysis, moderate/severe TR was associated with 2-fold higher mortality at 1-year follow up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, 4.9% of the patients had concomitant moderate/severe MR and 8% had concomitant moderate/severe TR. The key findings of our analysis are summarized in the following: (1) Moderate/severe TR was associated with higher all-cause mortality at 1-year follow up; (2) Moderate to severe MR did not affect mortality at follow up; (3) Neither significant MR nor TR affected the TAVI procedure success or in-hospital death; (4) In multivariate analysis, moderate/severe TR was associated with 2-fold higher mortality at 1-year follow up.…”
Section: Discussionmentioning
confidence: 99%
“…The most common valve heart disease in the western world is degenerative aortic valve stenosis (AS) (1). A significant proportion of patients receiving transcatheter aortic valve implantation (TAVI) have moderate or severe mitral regurgitation (MR) and/or tricuspid regurgitation (TR).…”
Section: Introductionmentioning
confidence: 99%
“…This probably increases sensitivity for auscultation as the prevalence of more advanced disease is higher in such patient samples. Only two studies were done on an unselected population (Gardezi et al and Steeds et al ) 23 24…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the prevalence of significant AS in our study falls well in line with that reported in the ARIC study of 0.7% [ 51 ]. Even though some have argued for opportunistic screening for aortic valve disease [ 53 ], the cost-benefit of screening and following elderly at-risk patients with aortic sclerosis in unclear. Follow-up echocardiographic examinations in the LOOP study have now been concluded and may help to illustrate the extent to which aortic sclerosis progresses to AS in these participants.…”
Section: Discussionmentioning
confidence: 99%